The world as we knew it : dispatches from a changing climate - Brady, Amy; Isen, Tajja; Millet, Lydia, 1968-; Bellot, Gabrielle; Sudbanthad, Pitchaya; Rush, Elizabeth; Febos, Melissa; Raboteau, Emily; El Akkad, Omar, 1982-; Yuknavitch, Lidia; Subramanian, Meera; Johnson, Lacy M., 1978-; et al. (Catapult, 2022)
Including essays by Lydia Millet, Alexandra Kleeman, Omar El Akkad and others, this collection from literary writers around the world offer timely, haunting first-person reflections on how climate change has altered their lives.